Genetic programming for stacked generalization - Bakurov, Illya (2021)
Bakurov, I., Castelli, M., Gau, O., Fontanella, F., & Vanneschi, L. (2021). Genetic programming for stacked generalization. Swarm and Evolutionary Computation, 65, 1-14. [100913]. https://doi.org/10.1016/j.swevo.2021.100913